Quality Enhancement Cell and its Effectiveness: Khyber Pakhtunkhwa Universities’ Teachers and Students’ Perceptions and Expectations - Naeem Butt, Muhammad; Mansoor, Romina; Shafiq, Muhammad (The Journal of Humanities & Social Sciences, 2023)
The study encompassed perceptions and expectations of teachers and students regarding the efficacy of Quality Enhancement Cells (QECs) in 07 public sector universities of Khyber Pakhtunkhwa. The effectiveness of QECs was analyzed on 09 domains, standard criteria, set by HEC. The sample of the study comprised 105 teachers and 105 students selected through simple random sampling technique. Two closed-ended questionnaires were constructed consisting 34 question items, with same essence, one each for students and teachers. Gamma correlation coefficient technique was employed to analyze the data. The results of University of Peshawar revealed that QEC required improvement in the domains of implementation of plans, teachers’ evaluation by students, weaknesses rectified, and corrective actions taken by university, course evaluation and teaching department’s interaction with teachers regarding their evaluation and internal evaluation of teachers’ performance. The University of Agriculture Peshawar, UET Peshawar and UST Bannu did not achieve the required standards in any of the 09 domains. Results further elicited that QECs of Islamia College University Peshawar, Gomal University D.I. Khan and Kohat University of Science and Technology did not address the domains of membership of international bodies, participation of students in international events and external evaluation of teachers’ performance. The performance of QECs was not satisfactory in the selected universities.